2016
DOI: 10.1590/1678-4324-2016160506
|View full text |Cite
|
Sign up to set email alerts
|

Research on Phosphorus Removal in Artificial Wetlands by Plants and Their Photosynthesis

Abstract: Urban rainfall runoff pollution has become a major reason for water eutrophication problem in the process of urbanization in China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
(12 reference statements)
0
9
0
3
Order By: Relevance
“…0.05) results confirmed by Zhang et al (2007). The decrease of PO 3À 4 in the treated water for all units is caused by the uptake by gravel in the filter for the unplanted cell (Molle 2003;Sim 2003), and by the interaction of bacteria and plants (Quan et al 2016), but it is a very small amount (Lantzke et al 1998).…”
Section: Phosphorous Removalmentioning
confidence: 66%
“…0.05) results confirmed by Zhang et al (2007). The decrease of PO 3À 4 in the treated water for all units is caused by the uptake by gravel in the filter for the unplanted cell (Molle 2003;Sim 2003), and by the interaction of bacteria and plants (Quan et al 2016), but it is a very small amount (Lantzke et al 1998).…”
Section: Phosphorous Removalmentioning
confidence: 66%
“…A study in Brazil showed that emergent plants removed about 3.95 mgP/m 2 pollutants daily, which is responsible for removal of about 30.6% pollutants by artificial wetlands, while removal of the rest 69.1% pollutants are done by other means like substrates and microorganisms. The results indicate that in artificial wetlands, nitrogen rather than other pollutants was removed by other means like substrates and microorganisms (12).…”
Section: Introductionmentioning
confidence: 93%
“…Sự hấp thu chất ô nhiễm của thực vật giữ vai trò quan trọng trong quá trình xử lí nước thải của hệ thống đất ngập nước, nhưng quá trình này xảy ra không đáng kể đối với chỉ tiêu phosphate. Điều này cũng được minh chứng qua cơ chế loại bỏ PO 3− 4 trong mô hình đất ngập nước kiến tạo chảy mặt chủ yếu qua con đường lắng đọng [18]. Le Diem Kieu et al [19] cũng đã chứng minh được PO 3− 4 chủ yếu được giữ lại qua lớp cơ chất hay trên nền đáy của mô hình ĐNNKT.…”
Section: A Diễn Biến Nồng độ Phosphateunclassified
“…Tuy nhiên, ở ngày thứ 12, khả năng loại bỏ phosphate trong các nghiệm thức không đổi hoặc giảm so với ngày thứ 9, điều này dẫn đến nồng độ phosphate trong nước thải không giảm theo xu hướng mà tăng trở lại, có nghĩa là quá trình loại bỏ phosphate trong nước thải chủ yếu thông qua quá trình hấp phụ và lắng đọng trên nền đáy. Theo Quan et al [18], việc hấp phụ là quá trình đảo nghịch, khi nồng độ phosphate trong nước thải thấp, một tỉ lệ nhỏ chất bị hấp phụ sẽ bị khuếch tán trở lại môi trường, do lực tương tác kém, dẫn đến giảm tốc độ loại bỏ chất ô nhiễm. Kết quả phân tích trong nghiên cứu phù hợp với các kết quả nghiên cứu được thực hiện trước đây [21], [22].…”
Section: A Diễn Biến Nồng độ Phosphateunclassified